EFFECTS OF PROTEIN MALNUTRITION ON THE THYROID FOLLICULAR CELL SIZE OF ALBINO RATS - Qureshi, Muhammad Imran; Draz, Umar; Feroze, Naseem; Jafri, Saghir A. (Journal of Ayub Medical College Abbottabad, 1998)
In this study, the effect of protein malnutrition and its reversal was observed in rats. A total of 80 male albino rats (Wistar strain) were used in this study. The animals of various groups were given isocaloric diet but the protein content of the diet varied from 2.5 to 20%. It was observed that protein malnutrition had an adverse though reversible effect on the thyroid follicular cell size of the albino rats. It is suggested that a similar study should be conducted to see the effects of PEM on the thyroid hormones as well to correlate our study with the function of the gland.